Pyramiden Afterlife: Sporadic revitalisation strategy - Glukhova, Anastasia (2016)
The goal of this project is to challenge the problematic of preservation and revitalisation through the example of Pyramiden, a remote abandoned settlement located in the Norwegian Svalbard archipelago. The framework of the project is determined by complexity of the site. The geopolitical context of Svalbard, history of Pyramiden, ecological situation, economic factors of energy and mineral industries are all aspects that raise questions of the sustainability and expediency of regenerating existing towns, issues of heritage and protection of artifacts from decay and natural risks as well as reuse. Due the dramatic rise of tourism and growing share in a post-industrial economy related to questionable practices revolving around coal mining, the island receives more and more visitors each year and can no longer remain an abandoned ghost town. Therefore the project focuses on the immediate future of the Pyramiden's afterlife. Background research on the conditions and possibilities of Pyramiden and the surrounding region has led to the idea of Dynamic or Sporadic Revitalisation. Instead of renovating and revitalising the town for new full time / permanent productive functioning, the project approach is to create a growing-shrinking dynamic scenario following the natural yearly cycles of the town. The problem is to implement new functions with consideration of location, cultural qualities, desolation and remoteness. The proposed strategy for next several years includes the creation of events through an international festival that is the seasonal highlight with peak activity. The creative method and main function for Sporadic Revitalisation lies in the performance arts, particularly experimental theatre productions. Thus the afterlife of Pyramiden takes the shape of theatre performances, appearing for just a short period and existing extremely intensively in immediate reflection of the local specificity of Pyramiden. The festival goal is to attract visitors, promote awareness of regional issues impacting contemporary ...